Nanoporous Gold Films Prepared by a Combination of Sputtering and Dealloying for Trace Detection of Benzo[a]pyrene Based on Surface Plasmon Resonance Spectroscopy - Li Wang; Xiu-Mei Wan; Ran Gao; Dan-Feng Lu; Zhi-Mei Qi (Sensors, 2017)
A wavelength-interrogated surface plasmon resonance (SPR) sensor based on a nanoporous gold (NPG) film has been fabricated for the sensitive detection of trace quantities of benzo[a]pyrene (BaP) in water. The large-area uniform NPG film was prepared by a two-step process that includes sputtering deposition of a 60-nm-thick AuAg alloy film on a glass substrate and chemical dealloying of the alloy film in nitric acid. For SPR sensor applications, the NPG film plays the dual roles of analyte enrichment and supporting surface plasmon waves, which leads to sensitivity enhancement. In this work, the as-prepared NPG film was first modified with 1-dodecanethiol molecules to make the film hydrophobic so as to improve BaP enrichment from water via hydrophobic interactions. The SPR sensor with the hydrophobic NPG film enables one to detect BaP at concentrations as low as 1 nmol·L−1. In response to this concentration of BaP the sensor produced a resonance-wavelength shift of ΔλR = 2.22 nm. After the NPG film was functionalized with mouse monoclonal IgG1 that is the antibody against BaP, the sensor’s sensitivity was further improved and the BaP detection limit decreased further down to 5 pmol·L−1 (the corresponding ΔλR = 1.77 nm). In contrast, the conventional SPR sensor with an antibody-functionalized dense gold film can give a response of merely ΔλR = 0.9 nm for 100 pmol·L−1 BaP.